1991
DOI: 10.1002/hep.1840130206
|View full text |Cite
|
Sign up to set email alerts
|

Carbon tetrachloride—induced alterations of hepatic calmodulin and free calcium levels in rats pretreated with chlordecone

Abstract: Calmodulin, a low molecular weight Ca2+ binding protein, regulates a large number of cell activities including cell division. Previous studies from our laboratory indicated excessive accumulation of Ca2+ in hepatocytes succeeded by rapid glycogen breakdown and suppressed cell division in rats receiving CCl4 after previous dietary exposure to 10 ppm chlordecone. Since calmodulin plays a major role in Ca2(+)-regulated events and has been reported to be localized in mitotic apparatus during cell division, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…This cisplatin-induced antitumor effect was reduced significantly by GJIC inhibition, which was consistent with the results from cell experiments, indicating that GJs function as tumor suppressors to restrict tumor growth. In the meantime, the therapeutic dose of cisplatin did not induce obvious increases in serum AST and ALT levels or histological damage, consistent with the report that the therapeutic dose of cisplatin did not cause detectable liver damage 24 . Together, these findings demonstrated that GJIC could potentiate the antitumor effect of cisplatin in vivo without enhancing hepatic damage.…”
Section: Discussionsupporting
confidence: 90%
“…This cisplatin-induced antitumor effect was reduced significantly by GJIC inhibition, which was consistent with the results from cell experiments, indicating that GJs function as tumor suppressors to restrict tumor growth. In the meantime, the therapeutic dose of cisplatin did not induce obvious increases in serum AST and ALT levels or histological damage, consistent with the report that the therapeutic dose of cisplatin did not cause detectable liver damage 24 . Together, these findings demonstrated that GJIC could potentiate the antitumor effect of cisplatin in vivo without enhancing hepatic damage.…”
Section: Discussionsupporting
confidence: 90%